Production potential of the first generation of selected Pitalah and Bayang ducks as a community economic resource in West Sumatra (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: This study aimed to measure the production potential of selected Pitalah and Bayang male ducks and their first generation. Materials and Methods: A total of 100 Pitalah and 100 Bayang 1-day-old ducks (40 males, 60 females) were obtained from local farmers and reared for 32–34 weeks. Twenty male ducks were selected as parental ducks based on their body weight (BW) and feed conversion ratio (FCR) at weeks 8 and 12. Forty female layer ducks were selected as parental ducks based on their blood cholesterol levels. Selected parental ducks were allowed to reproduce, and the ducklings were reared for 8 weeks before their BW, BW gain (BWG), feed intake, FCR, carcass weight percentage, abdominal fat percentage, and income over feed and duck cost (IOFC) ratio were measured. The data were subjected to a t-test. Results: Pitalah parental and first-generation ducks had better production performance and blood lipid profiles than Bayang ducks (p < 0.05). Based on the IOFC ratio, rearing Pitalah ducks for 8 weeks for meat production was more profitable and beneficial as a community economic resource. Conclusion: The selection of Pitalah and Bayang ducks was worth pursuing, as the G1 of both Pitalah and Bayang ducks had better production performance in terms of their BW, BWG, and FCR. Based on the IOFC values, raising Pitalah ducks for 8 weeks for meat production would be more economically beneficial.J. Adv. Vet. Anim. Res., 10(3): 378–384, September 2023http://doi.org/10.5455/javar.2023.j690